A Culture of Sexual Harassment: Anthropological research in the city of Baghdad - Abdul Sada Haider, Hilal (Al-Adab Journal, 2020)
Sexual harassment is one of the phenomena that has emerged in global societies alike and in Arab societies in particular, including the Iraqi society, It is not a modern phenomenon But it has worsened and increased widely in recent decades, This increase stems from several factors, including the openness of societies to each other and the fact that the world has become a very small global village, Various media outlets such as satellite TV, multiple TV channels and informational networks have performed, And social networking sites of all kinds, Which has clearly invaded Arab societies, especially Iraqi society, played an important role in the spread of the phenomenon of sexual harassment Promoting this phenomenon through advertisements in which women appear, whether they are commercial advertisements or advertisements in programs, The phenomenon of sexual harassment in Iraqi society may be hidden and undeclared, but it is abundant, Customs, traditions and social norms exert great pressure on women not to reveal and talk about sexual harassment, This is because women are prisoners of the traditions of society, Even women who seek freedom and deliverance from these restrictions (social norms) when they are exposed to sexual harassment, They cannot confront and respond, and most of the time, silence is the response to sexual harassment, As well as for several other social and ethical reasons and indicators, Therefore, one of the aims of the research was to identify the causes of sexual harassment in the research community, which consisted of a group of women who had been subjected to sexual harassment, In workplaces, public roads, malls, markets, schools and universities. The research was divided into two chapters, one and two, and in each chapter there are three sections: The first chapter is the theoretical framework for the research, and it includes three topics:The first topic: the main research elementsThe second topic: scientific research concepts and termsThe third topic: previous studiesThe second chapter: the theories explaining the research and forms of sexual harassment. Three topics are also fulfilled as follows:The first topic: research theoriesThe second topic: the causes of sexual harassmentThe third topic: procedures and tools for researchDescriptive approachThe most important tools were the interviewer and informantsThe research reached a number of results, including the following:1. The research community is characterized by an overwhelming phenomenon, which is the increase in the percentage of the young age group, which is the majority part of the research community.2. Women leaving the home for the purpose of meeting education or work constitutes a major role in women's exposure to sexual harassment.3. It is evident from the marital status that women who have not married are more vulnerable to harassment than others, which indicates the presence of impotence in marriage in Iraqi society.4. The research revealed that there is no relationship to the issue of sexual harassment with the type of housing, and that work, transportation routes, public roads and markets are the places where sexual harassment occurs most.5. It is evident from the research that the phenomenon of sexual harassment is increasing and increasing in Iraqi society, which requires a remedy for it and to reduce its risk.